2020
DOI: 10.9734/ajaees/2020/v38i430339
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Survey of Uttar Pradesh, Bihar and Maharashtra States of Indian Continent

Abstract: Dairy farming plays a very important role in improving the economy of rural India. The study was conducted to explore the socio-economic profile of dairy farmers and farmers feedback about dairy development project. The survey was conducted to study the education status, family structure, education status and management of animals, different patterns of rearing of dairy animals and status of milk production. Data was collected from the 3000 dairy farmers of three states namely Maharashtra, Bihar and Uttar Prad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…It's evident that there was high rate of diversification of crops among dairy sample households. These findings are comparable with similar findings reported by Potdar VV et al [6].…”
Section: Cropping Pattern Of Non-dairy Sample Households In Both Tran...supporting
confidence: 93%
See 2 more Smart Citations
“…It's evident that there was high rate of diversification of crops among dairy sample households. These findings are comparable with similar findings reported by Potdar VV et al [6].…”
Section: Cropping Pattern Of Non-dairy Sample Households In Both Tran...supporting
confidence: 93%
“…The cropping pattern followed by dairy sample households in [6] as ragi is the traditional crop and it is eaten as main staple food might have grown by majority of the respondents.…”
Section: Cropping Pattern Of Dairy Sample Households In Both Transectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formats were prepared for collecting the responses from the farmers. Details as of coverage area with other details are as [7] in his study reported majority of respondents were in middle age group. (2020) [7] reported The average size of family in the sample was 7.66 persons with 4.12 male members and 3.53 female www.extensionjournal.com members.…”
Section: Methodsmentioning
confidence: 95%
“…Details as of coverage area with other details are as [7] in his study reported majority of respondents were in middle age group. (2020) [7] reported The average size of family in the sample was 7.66 persons with 4.12 male members and 3.53 female www.extensionjournal.com members. State-wise differentials shows that on an average there were 8.74 members per household in Bihar, followed by Uttar Pradesh (6.76 members) and Maharashtra (6.17 members).…”
Section: Methodsmentioning
confidence: 95%